VD_FINDINFO AI 162/18 - 46/2019 vom 19. Februar 2019 - VD Tribunal cantonal (2019)
FENÊTRE{ÉLÉMENT DE LA CONSTRUCTION}, MOYEN AUXILIAIRE, TÉTRAPLÉGIE, SURDITÉ, AMÉNAGEMENT INTÉRIEUR | 21 LAI, 13.01 Annexe OMAI, 15.05 Annexe OMAI, 2 OMAI